Turkish Chemistry Teachers’ Views about Secondary School Chemistry Curriculum: A Perspective from Environmental Education - Omer Faruk Icoz (Journal of Education in Science, Environment and Health)
Teachers’ views about environmental education (EE) have been regarded as one of the most important concerns in education for sustainability. In secondary school chemistry curriculum, there are several subjects about EE embedded in the chemistry subjects in Turkey. This study explores three chemistry teachers’ views about to what extent the subjects related with EE should be integrated into secondary school chemistry curriculum at an individual level of analysis. The findings of the study indicate that there is a consensus among teachers on the inadequacy of secondary school chemistry curriculum for providing students an effective EE. However, there is an inconsiderable divergence among the teachers’ views about the placement of subjects about EE in chemistry curriculum and the integration of subjects about EE into the curriculum. Through the results of the study, policy makers and curriculum developers would gain a comprehensive insight about deficiencies in chemistry curriculum for EE from the point of view of chemistry teachers and they would have opportunity to realize the ways for the remedy of this deficiency.